A comparative analysis of the benefits of clips and series episodes as tools to strengthen oral comprehension of English lexical-grammatical features in the Teens Advanced group of the English courses at the Antonio Nariño University (2021)
The purpose of this study was to carry out a comparative analysis of clips and 20- minute series episodes when it comes to the benefits they offer as tools for strengthening oral comprehension from the lexical-grammatical aspect in the learning of English as a foreign language. To carry through, action research was carried out with the participation of the Teens advanced group of the English courses offered by Antonio Nariño University. Considering the most popular resources and taking into account the students' interest and to compare we chose clips and 20-minute series episodes for this project. The survey, on the one hand, was implemented to to know the degree of satisfaction students had; and the exams, on the other hand, to have a wider idea of the progress students can have when it comes to understanding lexical-grammatical links given in diverse communicative events taken from clips in comparison to those present in 20-minute series episodes